Produktivitas Primer Perairan Estuari Berdasarkan Kandungan Klorofil-a di Kecamatan Talawi Kabupaten Batu Bara (Primary Productivity of Estuarine Based On The Concentration of Chlorophyll-a at Kecamatan Talawi Kabupaten Batu Bara) - Tantri Ayu Syahfitri; Hesti Wahyuningsih; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Primary Productivity is the formation process of organic compounds through photosynthesis. This research aimed to know primary productivity based on the concentration of chlorophyll-a, phytoplankton identification and it’s abundance at the estuarine of Kecamatan Talawi Kabupaten Batu Bara. The water sampling is conducted three times in two weeks interval during April until Mei 2014. From the observation is known first station’s estuary classified as Well-mixed estuary is the estuary that completely mixed, second station’s estuary as Salt wedge estuary is the estuary that has weak mixing. The research results that there are 5 classes 17 families and 25 species of phytoplankton. The highest species abundance is 1073,889 ind/l found at third station, and the highest abundance species is Skeletonema sp. The highest chlorophyll-a value is 0,89 mg/m3 was found at third station.Keywords: productivity, chlorophyll-a, phytoplankton, Skeletonema sp., estuarine, Kecamatan Talawi.